An Arduino-Based System for Optimizing Solar Energy Generation - Akshay B Dumbare; Amol T Wagh; Rutik K Darane; Chetan P. Patil (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This project presents a low-cost, Arduino-based system for optimizing solar energy generation. The system utilizes a solar panel, a light-dependent resistor (LDR), and a servo motor to track the sun's movement and maximize energy harvesting. The Arduino microcontroller reads data from the LDR and controls the servo motor to adjust the solar panel's angle and orientation. The system's performance is evaluated based on its ability to track the sun's movement and generate maximum power. Experimental results show that the system can increase solar energy generation by up to 30% compared to a fixed solar panel. The proposed system offers a cost-effective and efficient solution for optimizing solar energy generation, making it suitable for various applications, including renewable energy systems and environmental monitoring.
Keywords: Arduino; solar energy; sun tracking; optimization; renewable energy